Skolotājs kā starpkultūru kompetenču veidošanās sekmētājs Turcijas skolās - Öfkeli, Bekir (Latvijas Universitāte, 2015)
In Turkey, multicultural education has gained importance. The ability to work effectively with diverse student populations is increasingly important for student affairs practitioners as schools become more diverse in their student populations. They must be competent enough to deliver a lecture to diverse groups. To help the teachers with their deficiencies it is important to research whether they are capable of managing cultural differences in their classrooms. Conceptual work of this study has been carried out on three research questions. The research questions in this study focused on three target groups : in-service teachers actively working in public schools, pre-service teachers(teacher-candidates) at Çukurova University and students at public schools in Adana.The research questions addressed the cultural competence of teachers, its impact, how it is acquired, and effective strategies for diverse students and investigated the relationships between teacher multicultural competencies and students’s cultural characteristics. This paper summarizes studies on the importance of preparing teachers to become culturally competent educators and describes the approach we used to evaluate the design for a course on diversity. The study also tries to explore pre-service teachers’perceptions of their strengths and deficiencies for working with, and meeting the need of, students from diverse cultural backgrounds justb before starting as an inservice teacher This research showed that teachers need more knowledge of multicultural education and teaching immigrants, which should be taken into account already in teacher education. There appears to be a need for knowledge of education and of practical skills of handling a culturally diverse classroom
Teacher as promoter of the development of multicultural competences in schools of Turkey
Keywords: Pedagoģija